2018
DOI: 10.1002/jcp.26427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restriction vegan diet's on muscle mass, oxidative status, and myocytes differentiation: A pilot study

Abstract: This study was conceived to evaluate the effects of three different diets on body composition, metabolic parameters, and serum oxidative status. We enrolled three groups of healthy men (omnivores, vegetarians, and vegans) with similar age, weight and BMI, and we observed a significant decrease in muscle mass index and lean body mass in vegan compared to vegetarian and omnivore groups, and higher serum homocysteine levels in vegetarians and vegans compared to omnivores. We studied whether serum from omnivore, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 48 publications
(57 reference statements)
5
48
1
Order By: Relevance
“…Third, the dietary habit or steroid intake can affect the muscle mass, but these factors were not controlled in our study. Previous studies were shown that dietary protein intake can accelerate protein synthesis in the muscle [30] and lean muscle mass was significantly lower in vegan than in non-vegan [31]. Androgenic steroid can increase the lean body mass and muscle strength [32].…”
Section: Plos Onementioning
confidence: 97%
“…Third, the dietary habit or steroid intake can affect the muscle mass, but these factors were not controlled in our study. Previous studies were shown that dietary protein intake can accelerate protein synthesis in the muscle [30] and lean muscle mass was significantly lower in vegan than in non-vegan [31]. Androgenic steroid can increase the lean body mass and muscle strength [32].…”
Section: Plos Onementioning
confidence: 97%
“…In recent decades, particular attention has been paid to the antioxidant or antiproliferative role of polyphenols [ 37 , 38 , 39 , 40 , 41 , 42 ] in the human diet, with evidence to support the contribution of polyphenols in the prevention of degenerative diseases [ 34 , 43 ]. Although oxidative stress has been observed during aging [ 44 , 45 ], under certain pathological conditions [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ] or contractile activity [ 53 , 54 ], a number of studies have revealed that it is also related to the development of obesity. Excessive levels of reactive oxygen species (ROS) could lead to dysfunction of mitochondria by inhibiting the breathing process and resulting in reduced energy expenditure in adipocytes and, on the contrary, improvement of energy accumulation in adipose tissue.…”
Section: Polyphenols: Bioactive Compoundsmentioning
confidence: 99%
“…In addition, vegans also showed lower levels of leukocytes, lymphocytes, platelets, complement factor 3, and blood urea nitrogen, but higher levels of albumin. In 2018, a paper on the impact of a vegan diet on muscle mass, oxidative status and myocyte differentiation was published [9]. The effects of serum on the oxidative, growth and differentiation of both the H9c2 and H-H9c2 cardiomyoblast cell lines were compared, and the study showed that treatment with vegan sera of both H9c2 and H-H9c2 cells induced an increase in TBARS, a marker of lipid peroxidation, compared to vegetarian sera and omnivores.…”
Section: Advantages and Disadvantages Of A Vegan Dietmentioning
confidence: 99%
“…Vegan diets are lower in total fat and saturated fat [9], and are also richer in Ω-6 fats. Studies have shown that a low-fat diet can negatively affect testosterone levels in men.…”
Section: Fatsmentioning
confidence: 99%